An economic assessment of airport incentive regulation. (July 2015) - Adler, Nicole; Forsyth, Peter; Mueller, Juergen; Niemeier, Hans-Martin
Abstract: There has been a gradual trend towards incentive regulation of airports since the privatization of BAA in 1986. Airports are price capped in several countries belonging to the European Union, as well as elsewhere, notably India. However, most of the price caps are not a pure price cap in which the X-factor is set independently of the cost of the regulated airport. Typically, hybrid price caps are used and combined with sometimes complex mechanisms like sliding scales, quality incentives and investment obligations, such that the incentive structures may become distorted. We provide an overview of the changes in the governance structure of airports as a result of privatization, analyze how far the regulatory institutions obey the principles of 'good' regulation, such as fairness and transparency, and investigate the performance of the new regulation in terms of allocative efficiency by reviewing benchmarking studies. Finally, we assess the impact of incentive regulation on productive efficiency using data envelopment analysis and second stage regression, which suggests that incentive regulation is superior to cost plus.